Fixed Point Results for Generalized $α$-Admissible Almost Type $\mathcal{Z}$-Contractions - Deng, Jia; Liu, Xiao-lan; Sun, Yan (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we present several types of generalized $α$-admissible almost type $\mathcal{Z}$-contractions, which can be considered as the generalizations of $α$-admissible $\mathcal{Z}$-contractions and almost $\mathcal{Z}$-contractions, and obtain the fixed point results of these contractions in complete metric spaces. Moreover, we utilize some examples to verify the validity of main results. Finally, we give some fixed point results related to our results.